Gender and race issues in Zora Neale Hurston's novel Their Eyes Were Watching God - Bromová, Kristýna (Univerzita Pardubice, 2013)
The overall aim of this bachelor paper is to analyze gender and race issues in Zora Neale Hurston's work. In the first chapters the theories of gender and race as well as the description of Black English are defined. Next, the social background of Afro-Americans is outlined in the works of Afro-American writers, and a brief description of the Harlem Renaissance is made. Hurston's life and works are introduced, together with an introduction of the analyzed work. The most important part of the paper deals with the double oppression of black women - gender and race issues that are analyzed in the novel Their Eyes Were Watching God.
Otázka pohlaví a trasy v díle Zory Neale Hurston Their Eyes Were Watching God
Keywords: Afroameričané; Harlemská renesance; Hurstonová, Zora Neale; pohlaví; rasa; afroamerická angličtina; Afro-Americans; Harlem Renaissance; Hurston, Zora Neale; Their Eyes Were Watching God; gender; race; Black English